SCIENTIFIC AND THEORETICAL BASIS OF IMPLEMENTING THE COMPETENT APPROACH IN BIOLOGY EDUCATION - Sayyora Haytbaeva (The Bioscan, 2024)
Competence requires the ability of the student to constantly enrich his knowledge, absorb new information, feel the demands of the present, search for new knowledge, process it and use it in his practical work. Students with high competence can independently use the acquired knowledge, skills and abilities in their practical activities. Therefore, the introduction of competency-based approaches to the biology education processes of secondary schools and the achievement of educational efficiency are among the important tasks of today's education system. In this article, the scientific-theoretical basis of the introduction of competency-based approaches to biology education is highlighted, the concept of competency-based approach, the opinions of scientists who have researched the problem of competency-based approach, types of competency, and the principles of increasing the level of competence of students in biology education are highlighted.